Environmental Exosomes/Small Extracellular Vesicles: Evidence of Extracellular RNA Release by Aquatic Organisms - Ryo Yonezawa; Lingxin Meng; Naoki Hashimoto; Ibuki Igarashi; Satoshi Kimura; Nina Yasuda; Susumu Mitsuyama; Takanori Kobayashi; Kazutoshi Yoshitake; Shigeharu Kinoshita; Nahoko Bailey-Kobayashi; Kaoru Maeyama; et al. (Marine Biotechnology, 2026)

Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

Identification of dysregulated miRNA transcriptomic profile in canine hepatocellular carcinoma and comparison to human HCC - Saki Hashimoto; M.D. Nazmul Hasan; Mohammad Arif; Nobuhiro Nozaki; Al Asmaul Husna; Yu Furusawa; Takeshi Sogawa; Kaori Takahashi; Tomohide Kuramoto; Aki Noguchi; Masashi Takahashi; Md Mahfuzur Rahman; et al. (Research in Veterinary Science, 2025)

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

In vitro host relationships of ectomycorrhizal Tricholoma kakishimeji and closely related species reflect their habitat characteristics - Wataru Aoki; Naoki Endo; Yasushi Hashimoto; Mimori Tsuji; Tesuro Ito; Masaki Fukuda; Akiyoshi Yamada (Mycorrhiza, 2025)

Pressure-volume curves of fine roots reveal intraspecific variation across different elevations in a subalpine forest - Taiga Masumoto; Yuki Hashimoto; Takumi Ito; Koichi Takahashi; Naoki Makita (Journal of Plant Research, 2025)
Water conservation in fine roots can be important for the adaptation of trees to cold, nutrient-poor ecosystems. Although pressure–volume (p-v) curve traits are commonly used to assess leaf water conservation, little is known about their intraspecific variation in fine roots and their association with root functional traits, such as morphology and chemistry. Here, we aimed to determine the p-v curve traits of Betula ermanii and Abies mariesii fine roots at 2,000 and 2,500 m elevations and explore their intraspecific variation with root morphological and chemical traits in a subalpine forest. Turgor loss point (π tlp ), relative water content at π tlp , osmotic potential at full hydration, and capacitance at full turgor (C ft ) were evaluated as p-v curve traits. Additionally, root diameter, specific root length, and root tissue density (RTD) were assessed as morphological traits, and nitrogen (N) content was measured as a chemical trait. For A mariesii roots, the C ft was lower, and π tlp was more negative at 2,500 m than at 2,000 m. The p-v curve traits of B ermanii roots remained unchanged with elevation. There were strong correlations between RTD and π tlp and between N content and π tlp and C ft , especially for A. mariesii . These results indicated A. mariesii adjusted p-v curve traits with RTD and N content and achieved water conservation in fine roots at higher elevations. The p-v curve traits, particularly π tlp and C ft , reflected diverse tree strategies for environmental acclimation with fine-root carbon economy. Our findings highlighted the importance of adjusting water relation traits for acclimation to cold and nutrient-poor subalpine regions, particularly for evergreen coniferous species. The p-v curve traits revealed diverse fine-root water relation traits as a basis for water conservation capacity by preserving root function under stress conditions and enabling prolonged resource acquisition in a subalpine forest.

Effects of water temperature and infection history on the severity of summer atrophy in juvenile Akoya pearl oyster Pinctada fucata martensii - Naoki Hashimoto; Tomomasa Matsuyama; Yasunori Iwahashi; Kiyohito Nagai (Fisheries Science, 2025)

Anti-biofouling performance and microbial communities of an integrated fixed-film activated sludge membrane bioreactor with a fibrous carrier material: Pilot-scale demonstration - Hiroyuki Yoshino; Hop Van Phan; Naomichi Mori; Naoki Ohkuma; Masaki Kawakami; Masahiko Nihei; Satoshi Hashimoto; Ken Wakabayashi; Tomoyuki Hori; Akihiko Terada (Science of The Total Environment, 2024)

The composition of non-structural carbohydrates affects the respiration and morphology of tree fine roots in Japan Alps - Yuki Hashimoto; Naoki Makita; Masako Dannoura; Shitephen Wang; Koichi Takahashi (Rhizosphere, 2023)

Sex-Specific Differences in the Transcriptome of the Human Dorsolateral Prefrontal Cortex in Schizophrenia - Zhiqian Yu; Kazuko Ueno; Ryo Funayama; Mai Sakai; Naoki Nariai; Kaname Kojima; Yoshie Kikuchi; Xue Li; Chiaki Ono; Junpei Kanatani; Jiro Ono; Kazuya Iwamoto; et al. (Molecular Neurobiology, 2023)

Sublingual immunotherapy for 4 years increased the number of Foxp3+ Treg cells, which correlated with clinical effects - Tetsuya Terada; Masaya Matsuda; Miki Inaba; Junpei Hamaguchi; Naoki Takemoto; Yusuke Kikuoka; Yuko Inaka; Harumi Sakae; Kennosuke Hashimoto; Hayato Shimora; Kazuyuki Kitatani; Ryo Kawata; et al. (Inflammation Research, 2021)

Consumption of lycopene-rich tomatoes improved glucose homeostasis in rats via an increase in leptin levels - Naoto Hashimoto; Naoki Tominaga; Manabu Wakagi; Yuko Ishikawa-Takano (Journal of Natural Medicines, 2020)

EcoBalance 2018—Nexus of ideas: innovation by linking through life cycle thinking (9–12 October 2018, Tokyo, Japan) - Shinsuke Murakami; Jun Nakatani; Kenichi Nakajima; Eri Amasawa; Ryota Ii; Kiyotada Hayashi; Naoki Yoshikawa; Ichiro Daigo; Yusuke Kishita; Tomohiko Ihara; Koichi Shobatake; Yuki Kudoh; et al. (The International Journal of Life Cycle Assessment, 2019)

EcoBalance 2016-responsible value chains for sustainability (October 3-6, 2016, Kyoto, Japan) - Keisuke Nansai; Masaharu Motoshita; Ichiro Daigo; Seiji Hashimoto; Kiyotada Hayashi; Keiichiro Kanemoto; Aiichiro Kashiwagi; Yoshinori Kobayashi; Shinsuke Kondo; Yuki Kudoh; Yasunari Matsuno; Hiroki Tanikawa; et al. (The International Journal of Life Cycle Assessment, 2017)

Factors influencing adherence to nasal continuous positive airway pressure in obstructive sleep apnea patients in Japan - Akihito Uematsu; Tsuneto Akashiba; Fumio Kumasawa; Toshiki Akahoshi; Naoki Okamoto; Kenichi Nagaoka; Yasuhiro Gon; Yoshitaka Kaneita; Makoto Uchiyama; Shu Hashimoto (Sleep and Biological Rhythms, 2016)

Involvement of GABAA receptors in 5-HT1A and σ1 receptor synergism on prefrontal dopaminergic transmission under circulating neurosteroid deficiency - Yukio Ago; Shigeru Hasebe; Naoki Hiramatsu; Kazuya Mori; Yuji Watabe; Yusuke Onaka; Hitoshi Hashimoto; Kazuhiro Takuma; Toshio Matsuda (Psychopharmacology, 2016)

Timing of the G1/S transition in tobacco pollen vegetative cells as a primary step towards androgenesis in vitro - Masaharu Kyo; Ai Nagano; Naoki Yamaji; Yuhki Hashimoto (Plant Cell Reports, 2014)

Neural population representation hypothesis of visual flow and its illusory after effect in the brain: psychophysics, neurophysiology and computational approaches - Hide-aki Saito; Eiki Hida; Shun-ichi Amari; Hiroshi Ohno; Naoki Hashimoto (Cognitive Neurodynamics, 2012)

Activation of metabotropic glutamate 2/3 receptors attenuates methamphetamine-induced hyperlocomotion and increase in prefrontal serotonergic neurotransmission - Yukio Ago; Ryota Araki; Koji Yano; Naoki Hiramatsu; Toshiyuki Kawasaki; Shigeyuki Chaki; Atsuro Nakazato; Hirotaka Onoe; Hitoshi Hashimoto; Akemichi Baba; Kazuhiro Takuma; Toshio Matsuda (Psychopharmacology, 2011)

Immunohistochemical localization of mitochondrial fatty acid β-oxidation enzymes in Müller cells of the retina - Kimie Atsuzawa; Ayami Nakazawa; Kenmei Mizutani; Motoaki Fukasawa; Naoki Yamamoto; Takashi Hashimoto; Nobuteru Usuda (Histochemistry and Cell Biology, 2010)

Constituents of the lichen Peltigera dolichorrhiza - Kazuko Yoshikawa; Erika Kunioka; Naoki Kokudo; Toshihiro Hashimoto (Journal of Natural Medicines, 2010)

Dynamic morphologies of pollen plastids visualised by vegetative-specific FtsZ1–GFP in Arabidopsis thaliana - Makoto T. Fujiwara; Haruki Hashimoto; Yusuke Kazama; Tomonari Hirano; Yasushi Yoshioka; Seishiro Aoki; Naoki Sato; Ryuuichi D. Itoh; Tomoko Abe (Protoplasma, 2010)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Characterization of a cry2A Gene Cloned from an Isolate of Bacillus thuringiensis serovar sotto - Jun Sasaki; Shinichiro Asano; Naoki Hashimoto; Bibiana W. Lay; Sugyo Hastowo; Hisanori Bando; Toshihiko Iizuka (Current Microbiology, 1997)